ENSEMBLES MUSICAUX REPRÉSENTATIFS DE LA PHILHARMONIE « TRANSILVANIA » DE CLUJ-NAPOCA. LES QUATORS À CORDES PENDANT LES ANNÉES 1955 – 1989 - Simona-Mihaela SPIRIDON (Studia Universitatis Babeş-Bolyai. Musica)
The string quartets, along with the brass quintet, the chamber orchestra, the ensembles “Ars Nova” and “Ars Antiqua” of the State Philharmonic in Cluj, founded in September 1955 at the initiative of conductor Antonin Ciolan, represent valuable points in cultural history of the city and the country. The “Napoca” Quartet was the first chamber music ensemble to be founded only a year after the philharmonic orchestra, enjoying the presence of the concertmaster Ştefan Ruha since 1964. The “Pro camera” Quartet is the second string quartet to appear in chronological order in the musical activity of the Philharmonic of Cluj in 1967. The “Concordia” Quartet was formed in 1971 at the initiative of the young violinist Andrei Agoston. Considered one of the most prestigious Romanian chamber ensembles that have captured the audiences worldwide, the “Transilvan” Quartet first appeared on stage in Cluj in 1985 under the name “Allegro”.